Naming the Deity, Naming the City: Rama and Ayodhya - Deepak Mehta (South Asia Multidisciplinary Academic Journal)
This paper studies the predicates associated with the name of the Hindu god Rama, as they come to inhabit the temple town of Ayodhya. My intention is to show how the name Rama is linked to the topography of Ayodhya, but also to a landscape that is marked by the absence of the Babri Mosque, demolished by members of the Hindu right in 1992. The name Rama imagines Ayodhya to be both a pastoral setting and a site of national regeneration. This is achieved by coupling the architectural spaces of Ayodhya to the many names of Rama, and to his kingdom. I suggest that the Rama deity, installed in the place of the mosque, acquires life in this combination.